Post‐transplant recurrence of atypical hemolytic uremic syndrome in a patient with thrombomodulin mutation. (30th September 2013) - Sinibaldi, Serena; Guzzo, Isabella; Piras, Rossella; Bresin, Elena; Emma, Francesco; Dello Strologo, Luca
Abstract: HUS is characterized by hemolytic anemia, thrombocytopenia, and acute renal failure. While "typical" HUS is usually associated with Shiga toxin‐producing Escherichia coli infections and recovers in the majority of cases, aHUS is caused by mutations of complement components or antibodies against CFH leading to uncontrolled activation of alternative complement pathway and often to ESRD. Recently, THBD gene mutations have been reported in aHUS. Theoretically, the risk of disease recurrence after renal transplantation should be low because THBD is primarily a membrane‐bound protein expressed by endothelial cells; however, a small proportion of THBD is present as a soluble form in plasma. We report the case of a 19‐yr‐old man with aHUS secondary to a THBD mutation that relapsed twice after two renal transplantations performed 12 yr apart. Despite successful control of HUS with plasma exchange and eculizumab after the second transplantation, the graft was ultimately lost due to severe steroid‐resistant cellular rejection. The present report suggests that THBD mutations may favor‐relapse of aHUS after renal transplantation.